Applying the nutrient transfer continuum framework to phosphorus and nitrogen losses from livestock farmyards to watercourses. Issue 6 (5th October 2021) - Vero, Sara E.; Doody, Donnacha
Abstract: Farmyards are commonly conceptualized as point sources of nutrient pollution nested within the wider agricultural landscape. However, within farmyards there are individual sources and delivery pathways, each of which is affected by a range of management practices and infrastructure. Rainfall mobilizes these nutrients, which may then be delivered to a receptor or to the wider drainage network. As such, the nutrient transfer continuum (NTC), which has been established as a framework to understand and mitigate nutrient loss at a landscape scale, can be similarly applied to disentangle the stages of nutrient transfer from farmyards. The NTC differentiates nutrient transfer into source, mobilization, delivery, and impact stages. This differentiation allows targeting of mitigation measures and evaluation of costs and benefits. This review paper applies the NTC template to farmyard nitrogen and phosphorus transport to conceptualize causative factors and to identify mitigation options. Core Ideas: The nutrient transfer continuum framework is applied to farmyard N and P losses. Nutrient sources include urine, feces, silage effluent, and parlor washings. Mobilization is controlled by the timing and magnitude of rainfall. Delivery is controlled by connectivity of the farmyard with the drainage network. Mitigation measures include management and infrastructure.